Communication and conversion in northern Cameroon : the Dii people and Norwegian missionaries, 1934-1960 - Drønen, Tomas Sundnes. (Studies in Christian Mission, 2009)
Was modern Christian mission to Africa primarily a colonial project and a civilizing mission or was it a spiritual revival spreading to new areas? This book tells the tale of the Dii people in northern Cameroon and describes their encounter with Norwegian missionaries. Through archival studies and through fieldwork among the Dii, an intriguing scenario is presented. Whereas the missionaries describe their mission as one of spiritual liberation, and the Dii highligt the social liberation they received through literacy and political independence, the author shows how both spiritual and social changes were results of captivation, miscommunication and constant negotiations between the two parties.